2017
DOI: 10.1007/s12571-016-0646-y
|View full text |Cite
|
Sign up to set email alerts
|

Young people’s perspectives on farming in Ghana: a Q study

Abstract: An emerging orthodoxy suggests that agriculture is the key to addressing the youth employment challenge in Africa. The analysis that informs this orthodoxy identifies a number of persistent barriers to increased productivity; and the programmes that work to get young people engaged with agriculture make assumptions about the young people's interests and behaviours. In this paper we report results from a study with secondary students in Ghana using Q Methodology. The objective was to determine to what degree th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 15 publications
3
64
0
Order By: Relevance
“…The crop farming-based livelihoods depend on supportive processes such as culture of sustaining institutions in form of resource governance structures [34,36] such as the local CRBs and VAGs which would be useful for crop protection and elephant management. This study revealed that such processes were feeble and largely restricted to family ties and clans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crop farming-based livelihoods depend on supportive processes such as culture of sustaining institutions in form of resource governance structures [34,36] such as the local CRBs and VAGs which would be useful for crop protection and elephant management. This study revealed that such processes were feeble and largely restricted to family ties and clans.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of functional institutions and with undue human pressure to overcome livelihood hardships, human resilience to conserve elephants may also eventually collapse [34,35]. The functional institutions of sustainability would encompass various social governance elements inter alia functional governance structures, processes, policies, and norms relevant to elephant conservation [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…The two last topics were selected because they were regularly mentioned in other studies as topics that led young people to lose interest in farming (e.g. Asciutti et al, 2016;Sumberg et al, 2017;Tadele and Gella, 2012). The interviewees were invited to rank each topic as: (1) this is not an issue for me; (2) this is an issue for people in my village, but does not affect me personally; (3) this represents a slight disadvantage in my case; (4) this is a major constraint for me; and (5) this is an insurmountable obstacle and explains why I am not interested in farming.…”
Section: Methodsmentioning
confidence: 99%
“…In the international development community, there is a strong narrative that "the rural youth" in developing countries find farming unattractive and therefore opt out of farming when possible (Leavy & Hossain, 2014;Sumberg et al, 2017). 1 This perception has sparked much concern recently with growing evidence of a youth bulge in numerous developing countries, many of whom are located in Africa (Ahmed, 2016;Evoh, 2012;Sommers, 2011).…”
Section: Introductionmentioning
confidence: 99%